Cyclic Mastalgia among Sudan International University (SIU) medical students - Tarig Mohamed Fadl Elmula Fadl Alla; Hatim Osman; Hussein Ali; Riham Kamal Youssif Ahmed; Dalia Abdelfadiel Hamd; Mohamed Elmubarak Awadelkarim; Jasser Gorany; Nahla Mohamed Hmid Adam; Amged Gaffer Mostafa; Yagoub Abdelmajid Mohamed Kheir (International Journal of Medical Toxicology and Legal Medicine, 2025)
Background : Breast pain is a main concern for women of all ages. Mastalgia is the medical term for breast pain, ranging from minor discomfort to severely incapacitating pain. Purpose : The main purpose of this study was to study cyclic mastalgia among female medical students at Sudan International University. Methods : A descriptive cross-sectional facility-based study was conducted. Results : Three hundred-five female medical students were included in this study; the results revealed that the prevalence of cyclic mastalgia among them was 55%. Additionally, cyclic mastalgia found no significant difference between the cycle’s regularity and the age of menarche (p = 0.565 & 0.260, respectively). Moreover, a substantial association between indirect variables with mastalgia has been explored. Conclusions: It was concluded that mastalgia was a serious condition that greatly impacts daily activities and interferes with the psychological, social, and even sexual activity of female medical students at Sudan International University (SIU). This issue should be addressed at the university level to reduce the risks of its associated negative outcomes.